Composite particles for toner additives

By surface modification on metal oxide particles and adjusting their particle size distribution, shape and surface roughness, we form highly embedded metal oxide-polymer composite particles, which solves the problems of low embedded efficiency and particle shedding in soft polymers, and achieves better fluidity and three-body charge characteristics.

JP2025069220AActive Publication Date: 2025-04-30CABOT CORP
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2025009227
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2019-06-28
Filing Date
2025-01-22
Publication Date
2025-04-30
Estimated Expiration
2039-08-06

AI Technical Summary

Technical Problem

When existing metal oxide-polymer composite particles are embedded in soft polymers, the embedding efficiency is low, and larger particles are prone to fall off, affecting the printing quality of electro-optical images and the operation efficiency of the equipment.

Method used

Surface modification is performed by using a preliminary hydrophobic system containing a dual-function component on the metal oxide particles, which is connected to the polymer matrix by covalent bonding and form a polymer or copolymer in the polymer matrix. At the same time, by adjusting the particle size distribution, shape and surface roughness of the particles, the fluidity and three-body charge characteristics of the composite particles are improved.

Benefits of technology

The embedding efficiency of metal oxide-polymer composite particles in soft polymer is improved, the particle shedding phenomenon is reduced, the printing quality of electro-optical images and the operation efficiency of equipment is improved, and the fluidity and three-body charge characteristics of the composite particles are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025069220000001_ABST
    Figure 2025069220000001_ABST
Patent Text Reader

Abstract

To provide composite particles for toner additives.SOLUTION: Metal oxide-polymer composite particles have a median particle size of 40-75 nm or 100-150 nm and an average RTA of at least 0.06. Alternatively or additionally, metal oxide-polymer composites comprise two or more populations of metal oxide particles differing in size, particle size distribution, or shape. Alternatively or additionally, the use of a multicomponent hydrophobizing system including an alkylsilane to fabricate metal oxide-polymer composite particles increases the tribocharge of the composite particles.SELECTED DRAWING: Figure 8A
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the manipulation of particle size, morphology and triboelectric charging of metal oxide-polymer composite particles. [Background technology]

[0002] The formation of an electrophotographic image involves uniformly charging the surface of a photoreceptor drum or belt; exposing the photoreceptor surface to light to form a charge pattern on the photoreceptor surface, i.e., a latent image that mirrors the information to be transferred to the actual image; developing the latent image with electrostatically charged toner particles comprising a colorant dispersed in a binder resin; transferring the developed toner onto a substrate, such as paper; fixing the image onto the substrate; and preparing the photoreceptor surface for the next cycle by removing residual electrostatic charge and cleaning the residual toner particles from the photoreceptor drum.

[0003] Toners for use in electrophotography and electrostatic printing include binder resins and colorants, and may further include charge control agents, offset inhibitors, and other additives. External toner additives, such as metal oxide particles, are often combined with toner particles to improve selected properties of the toner particles, including flowability, transferability, adhesion, and cleaning properties. Different external additives may be used in one toner composition to improve various properties of the toner. For example, some additives may be selected to improve charging properties, i.e., triboelectric charging properties. Others may be selected to improve cleaning performance or humidity resistance. Of course, it is preferable that toner additives optimized for one function do not cause any adverse effects on the functions provided by different additives.

[0004] One function provided by toner additives is fluidity maintenance and spacing. If the toner particles stick to each other, they will not flow well; additives act to reduce the cohesion of the toner powder. Additive particles tend to be hard. On the other hand, toners are formed from softer polymers. The resulting agglomeration of toner particles is detrimental to both the operation of the electrophotographic device and the print quality. In fact, when manufacturers have tried to reduce the energy required to produce a printed page, they have turned to softer polymers (e.g., lower Tg polymers) to reduce the amount of heat required to fuse the toner to the substrate. However, hard additive particles can become embedded in soft toner particles, reducing the effectiveness of the additive. Increasing the particle size of the additive particles reduces embedding; however, larger particles are also heavier and exhibit a higher percentage of drop-off from the toner particles. Naturally, additive particles that have dropped off the toner cannot provide their function as part of the toner composition. The metal oxide-polymer composite particles described in US Patent No. 9,568,847 act as spacers between toner particles while exhibiting both limited embedding in the toner particles and limited drop-off. It is now desirable to further manipulate the roughness, shape and particle size of the metal oxide composite particles to improve the free-flowing performance of the metal oxide composite particles and to manipulate their triboelectric charging properties and refractive index. Summary of the Invention

[0005] In one embodiment, the metal oxide-polymer composite particles in powder form comprise a plurality of metal oxide particles and a polymer matrix; the metal oxide particles are surface-modified with a first hydrophobization system comprising a bifunctional component, through which the metal oxide particles are covalently bonded to the polymer matrix; the polymer of the polymer matrix is ​​a polymer or copolymer of the bifunctional component; and the metal oxide-polymer composite particles have a volume weighted median particle size D50 of 40-75 mm and an average RTA of at least 0.06, e.g., 0.06-0.019, 0.08-0.015, or 0.08-0.13.

[0006] Alternatively, the metal oxide-polymer composite particles in powder form comprise a plurality of metal oxide particles and a polymer matrix; the metal oxide particles are surface-modified with a first hydrophobization system comprising a bifunctional component, through which the metal oxide particles are covalently bonded to the polymer matrix; the polymer of the polymer matrix is ​​a polymer or copolymer of the bifunctional component; and the metal oxide-polymer composite particles have a volume weighted median particle size D50 of 100-150 nm and an average RTA of at least 0.06, e.g., 0.06-0.019, 0.08-0.015, or 0.08-0.13.

[0007] For any of these composite particles, the metal oxide particles may have a unimodal particle size distribution. The composite particles may have an average particle size roughness greater than 1.22, such as greater than 1.25, or up to 1.35, 1.60, 1.70, or 1.90. At least a portion of the surface of the metal oxide-polymer composite particles is modified with a second hydrophobizing agent. The metal oxide-polymer composite particles may contain at least 15% metal oxide.

[0008] The bifunctional component has the formula [R 3 3-x (OR 1 ) x ]SiR 2 Q, x is 1, 2 or 3, R 1 is methyl or ethyl, R 2is the general formula C n H 2n wherein n is 1 to 10; R 3 is methyl or ethyl, Q is a substituted or unsubstituted vinyl, acrylate ester or methacrylate ester group, with the proviso that when Q is a substituted or unsubstituted vinyl, n is from 2 to 10. The first hydrophobization system may further comprise a monofunctional moiety, e.g., a silane, covalently bonded to the metal oxide particle. The monofunctional moiety may be of the formula (OR 1 ) 4-z SiR 4 z R 1 is methyl or ethyl, z is 1 or 2, R 4 is a branched or unbranched C1 to C10 alkyl group or R 2 Ph, where Ph is an unsubstituted phenyl group or a phenyl group substituted with C1-C10 branched or unbranched alkyl, halogen, C1-C10 alkyl ether, methoxy, ethoxy, or hydroxy.

[0009] Any of the composite particles described above can be disposed against the surface of a toner particle to form a toner composition.

[0010] In another embodiment, the toner composition comprises toner particles mixed with a powder comprising metal oxide-polymer composite particles comprising a plurality of metal oxide particles and a polymer matrix. The metal oxide particles are surface modified with a first hydrophobizing system comprising a difunctional component through which the metal oxide particles are covalently bonded to the polymer matrix and a monofunctional component covalently bonded to the metal oxide particles. At least a portion of the surface of the metal oxide-polymer composite particles is modified with a second hydrophobizing agent, and the polymer of the polymer matrix is ​​a polymer or copolymer of the difunctional component. The triboelectric charge of the toner at HH conditions is at least 9% greater than the triboelectric charge of a toner comprising a control metal oxide-polymer composite in which the monofunctional component is replaced with the difunctional component.

[0011] Alternatively or in addition, the triboelectric charging of the toner at LL conditions is at least 10% greater than the triboelectric charging of a toner comprising a control metal oxide-polymer composite in which the monofunctional component is replaced with a difunctional component. Both the monofunctional component and the difunctional component may comprise a silane group. The monofunctional component may be represented by the formula (OR 1 ) 4-z SiR 4 z R 1 is methyl or ethyl, z is 1 or 2, R 4 is a branched or unbranched C1 to C10 alkyl group. The solubility of the monofunctional component may be 10 to 0.06 g / L, preferably 9 to 0.03 g / L, more preferably 8 to 0.1 g / L, and most preferably 7 to 0.5 g / L.

[0012] In another aspect, a method of making composite particles includes the steps of preparing an aqueous dispersion comprising metal oxide particles and a first hydrophobization system comprising a bifunctional component and a monofunctional component, where the bifunctional component and the monofunctional component are chemically bonded to the metal oxide particles; adding a polymerization initiator to the aqueous dispersion to form metal oxide-polymer composite particles having metal oxide particles on surfaces thereof, where the polymer matrix of the metal oxide-polymer composite particles is a polymer or copolymer of the first hydrophobization system; and drying the metal oxide-polymer composite particles to form a powder.

[0013] The method further comprises treating the metal oxide-polymer composite particles with a second hydrophobizing agent before or after the drying step to produce hydrophobized metal oxide-polymer composite particles. The monofunctional and bifunctional components may both contain silane groups. The monofunctional component is represented by the formula (OR 1 ) 4-z SiR 4 z R 1 is methyl or ethyl, z is 1 or 2, R 4 is a branched or unbranched C1-C10 alkyl group. The bifunctional component is represented by the formula [R3 3-x (OR 1 ) x ]SiR 2 Q, x is 1, 2 or 3, R 1 is methyl or ethyl, R 2 is the general formula C n H 2n wherein n is 1 to 10; R 3 is methyl or ethyl, Q is a substituted or unsubstituted vinyl, acrylate ester or methacrylate ester group, with the proviso that when Q is substituted or unsubstituted vinyl, n is 2 to 10. The dispersion may further comprise one or more of styrene, substituted or unsubstituted acrylate or methacrylate monomers, olefin monomers, vinyl esters or acrylonitrile. The solubility of the monofunctional component may be 10 to 0.06 g / L, preferably 9 to 0.03 g / L, more preferably 8 to 0.1 g / L, and most preferably 7 to 0.5 g / L.

[0014] In another embodiment, the metal oxide-polymer composite particles in powder form may include a plurality of metal oxide particles and a polymer matrix. The plurality of metal oxide particles includes at least a first group of metal oxide particles and a second group of metal oxide particles, the first group of metal oxide particles having a different particle size, shape or particle size distribution relative to the second group. The metal oxide particles are surface-modified with a first hydrophobization system including a bifunctional component through which the metal oxide particles are covalently bonded to the polymer matrix, a portion of the plurality of metal oxide particles are embedded in and protrude from the polymer matrix (i.e., at least a portion of the plurality of metal oxide particles protrude in and out of the polymer matrix, which may include at least a portion of each group of metal oxide particles), the polymer matrix includes a polymer or copolymer of the first hydrophobization system, at least a portion of the surface of the metal oxide-polymer composite particles is modified with a second hydrophobization agent, and the metal oxide-polymer composite particles have an average SF-1 of 110-185 and an average RTA of 0.06-0.19.

[0015] The first hydrophobization system may further comprise a monofunctional moiety, e.g., a silane, which is covalently bonded to the metal oxide particle. The bifunctional moiety has the formula [R 3 3-x (OR 1 ) x ]SiR 2 Q, x is 1, 2 or 3, R 1 is methyl or ethyl, R 2 is the general formula C n H 2n wherein n is 1 to 10; R 3 is methyl or ethyl, Q is a substituted or unsubstituted vinyl, acrylate ester, or methacrylate ester group, with the proviso that when Q is a substituted or unsubstituted vinyl, n is 2 to 10. Monofunctional components are represented by the formula (OR 1 ) 4-z SiR 4 z R 1is methyl or ethyl, z is 1 or 2, R 4 is a branched or unbranched C1 to C10 alkyl group or R 2 Ph, where Ph is an unsubstituted phenyl group or a phenyl group substituted with C1-C10 branched or unbranched alkyl, halogen, C1-C10 alkyl ether, methoxy, ethoxy, or hydroxy.

[0016] The volume weighted median particle diameters D50 of the first and second groups may have a ratio of about 40:1 to about 1.5:1. The width of the volume weighted particle diameter distribution described by the ratio D75 / D25 for the first and second groups may have a ratio of about 40:1 to about 1.1:1. The mass ratio of the first and second groups may be about 1:20 to about 20:1, such as about 1:15 to about 15:1, about 1:10 to about 10:1, about 1:5 to about 5:1, or about 1:2 to about 2:1. The metal oxide-polymer composite particles may have a volume weighted median particle diameter D50 of about 20 nm to about 1000 nm. The metal oxide-polymer composite particles may have an average roughness P of about 1.22 to about 1.9. 2 / 4πS, where P is the perimeter of the image of the metal oxide-polymer composite particle and S is the area of ​​the particle image, both P and S being determined from transmission electron micrographs. The polymer matrix may include polymers of styrene, unsubstituted or substituted acrylates or methacrylates, olefins, vinyl esters and acrylonitrile, as well as copolymers and mixtures of the above. The composite particles may be disposed on the surface of a toner particle to form a toner composition.

[0017] In another embodiment, a method of making metal oxide-polymer composite particles includes providing an aqueous dispersion comprising a first hydrophobization system in an aqueous medium and at least a first population of metal oxide particles and a second population of metal oxide particles, wherein the first population of metal oxide particles has a different particle size, shape or particle size distribution than the second population, and wherein the first hydrophobization system has a formula [R 3 3-x (OR 1 ) x ]SiR 2Q is a difunctional moiety having x=1, 2, or 3; R 1 is methyl or ethyl, R 2 is the general formula C n H 2n wherein n is 1 to 10, and R 3 is methyl or ethyl, and Q is a substituted or unsubstituted vinyl, acrylate ester, or methacrylate ester group, with the proviso that when Q is substituted or unsubstituted vinyl, n is from 2 to 10; incubating the dispersion for a predetermined period of time; adding a radical initiator to the dispersion; making the chemical groups of the first hydrophobizing system part of the polymer, thereby forming metal oxide-polymer composite particles; and drying the metal oxide-polymer composite particles to obtain a powder.

[0018] The method may further comprise the step of treating at least a portion of the metal oxide particles with a second hydrophobizing agent, which may be carried out before the step of preparing the metal oxide-polymer composite particles or after the step of forming the metal oxide-polymer composite particles. The first hydrophobizing system may be represented by the formula (OR 1 ) 4-z SiR 4 z and R 1 is methyl or ethyl, z is 1 or 2, R 4 is a branched or unbranched C1 to C10 alkyl group or R 2 Ph, where Ph is an unsubstituted phenyl group or a phenyl group substituted with C1-C10 branched or unbranched alkyl, halogen, C1-C10 alkyl ether, methoxy, ethoxy, or hydroxy. The D50 of the first group and the second group may have a ratio of about 40:1 to about 1.5:1. The ratio D75 / D25 for the first group and the second group may have a ratio of about 40:1 to about 1.1:1. The mass ratio of the first group to the second group may be about 1:20 to about 20:1.

[0019] The emulsion may further include one or more of styrene, substituted or unsubstituted acrylate or methacrylate monomers, olefin monomers, vinyl esters, or acrylonitrile. At least a portion of each group of metal oxide particles may protrude in and out of the polymer matrix. The metal oxide-polymer composite particles may have a volume weighted median particle size D50 of about 20 nm to about 1000 nm. The intrinsic density of the metal oxide-polymer composite particles is about 30% to about 90% of the intrinsic density of the metal oxide as measured by helium pycnometer method. The metal oxide-polymer composite particles may have an average SF-1 of about 110 to about 185 and an average RTA of about 0.06 to about 0.19. The metal oxide-polymer composite particles may have an average roughness P of about 1.22 to about 1.9. 2 / 4πS.

[0020] It is to be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are intended to provide further explanation of the invention as claimed.

[0021] The invention will now be described with reference to several figures of the drawing. [Brief description of the drawings]

[0022] [Figure 1A] FIG. 2 is a schematic diagram illustrating the effect on particle size and roughness when metal oxide particles of different sizes are used to make metal oxide-polymer composite particles according to an embodiment of the present invention. [Figure 1B] FIG. 1 is a schematic diagram illustrating several measurements used for particle characterization using transmission electron microscopy. [Figure 2A] 1 is a transmission electron micrograph of metal oxide-polymer composite particles produced according to embodiments of the present invention. [Figure 2B] 1 is a transmission electron micrograph of metal oxide-polymer composite particles produced according to embodiments of the present invention. [Figure 3A]1 is a transmission electron micrograph of metal oxide-polymer composite particles produced according to embodiments of the present invention. [Figure 3B] 1 is a transmission electron micrograph of metal oxide-polymer composite particles produced according to embodiments of the present invention. [Figure 3C] 1 is a transmission electron micrograph of metal oxide-polymer composite particles produced according to embodiments of the present invention. [Figure 4A] 1 is a transmission electron micrograph of metal oxide-polymer composite particles produced according to embodiments of the present invention. [Figure 4B] 1 is a transmission electron micrograph of metal oxide-polymer composite particles produced according to embodiments of the present invention. [Figure 5A] 1 is a transmission electron micrograph of metal oxide-polymer composite particles produced according to embodiments of the present invention. [Figure 5B] 1 is a transmission electron micrograph of metal oxide-polymer composite particles produced according to embodiments of the present invention. [Figure 6A] 1 is a transmission electron micrograph of metal oxide-polymer composite particles produced according to embodiments of the present invention. [Figure 6B] 1 is a transmission electron micrograph of metal oxide-polymer composite particles produced according to embodiments of the present invention. [Figure 6C] 1 is a transmission electron micrograph of metal oxide-polymer composite particles produced according to embodiments of the present invention. [Figure 6D] 1 is a transmission electron micrograph of metal oxide-polymer composite particles produced according to embodiments of the present invention. [Figure 7] 1 is a transmission electron microscope photograph of colloidal silica. [Figure 8A] 1 is a set of graphs resulting from statistical modeling of cohesion rate versus particle size and additive average RTA at 15% additive coverage on a model toner. [Figure 8B]1 is a set of graphs resulting from statistical modeling of cohesion rate versus particle size and additive average RTA at 30% additive coverage on a model toner. [Figure 8C] 1 is a set of graphs resulting from statistical modeling of cohesion rate versus particle size and additive average RTA at 45% additive coverage on a model toner. [Figure 9] 1 is a graph showing the change in aggregation versus surface coverage for composite particles with different RTAs. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0023] In one embodiment, the preparation of metal oxide-polymer composite particles using a first hydrophobization system comprising a difunctional component and an alkyl-based monofunctional component results in particles capable of increasing the triboelectric charging of toners in which they are used as external additives.

[0024] In another embodiment, metal oxide-polymer composite particles having a volume weighted median particle size D50 of 40 to 75 nm, e.g., 40 to 70 nm or 40 to 65 nm, and an average RTA of at least 0.06, e.g., 0.06 to 0.019, 0.08 to 0.015, or 0.08 to 0.13, provide good free-flowing properties to toners in which they are used as external additives.

[0025] In another embodiment, metal oxide-polymer composite particles having a volume weighted median particle size D50 of 100-150 nm, e.g., 105-150 nm or 110-150 nm, and an average RTA of at least 0.06, e.g., 0.06-0.019, 0.08-0.015, or 0.08-0.13, can better promote anti-blocking in toner compositions while improving free flow relative to smoother spacer particles.

[0026] In another embodiment, the toner composition comprises toner particles mixed with a powder comprising metal oxide-polymer composite particles comprising at least two groups of metal oxide particles having at least different particle sizes, shapes or particle size distributions and a polymer matrix. The surfaces of the metal oxide particles are modified with a first hydrophobization system comprising a bifunctional component, through which the metal oxide particles are covalently bonded to a polymer. At least a portion of the first group of metal oxide particles, the second group of metal oxide particles, or both, protrude in and out of the polymer matrix, which is a polymer or copolymer of the first hydrophobization system. Such a mixture of two or more groups of metal oxide particles allows for the manipulation of particle size, graininess and shape of the resulting composite particles, as shown in FIG. 1A. In FIG. 1A, the combination of the first group of metal oxide particles 10 with larger metal oxide particles 12 or with smaller metal oxide particles 14 allows for the production of metal oxide composite particles 100, 120 and 140 having different particle sizes. Particles 140 are smaller than particles 100, which are smaller than composite particles 120. The schematic shows an equal ratio of metal oxides ( 10 , 12 and 14 ) and matrix material 16 .

[0027] Metal oxide particles suitable for use in the present invention include silica, alumina, ceria, molybdenum oxide, titania, zirconia, zinc oxide, iron oxide, including but not limited to magnetite (Fe3O4) and various forms of Fe2O3, niobium oxide, vanadium oxide, tungsten oxide, tin oxide, clay, or mixtures or mixed oxides of any two or more of these. For use as an external toner additive, typically the metal oxide particles include at least one of silica, alumina, and titania, such as silica and / or titania. The metal oxide particles may have two or more different particle sizes. For example, metal oxide particles with different compositions may have different particle sizes. Alternatively or in addition, particles of a particular metal oxide, such as silica particles, may have a bimodal or multimodal particle size distribution. Of course, mixtures of two different metal oxides with the same or different compositions and two or more different particle sizes, shapes, or particle size distributions may also be used.

[0028] When two different particle sizes are used, their volume weighted median particle size D50 may have a ratio of about 40:1 to about 1.5:1, for example about 35:1 to about 2:1, about 25:1 to about 2.5:1, about 20:1 to about 3:1, about 15:1 to about 4:1, or about 10:1 to about 5:1. D50 can be measured by disc centrifuge photosedimentometry or transmission electron microscopy. Alternatively or in addition, the metal oxide particles may have a bimodal or multimodal particle size distribution. The ratio of particle sizes corresponding to the peaks of the particle size distribution may be similar to those described above. Alternatively or in addition, the two or more metal oxide particles may have different shapes while having similar D50. Alternatively or in addition, the different metal oxide particles may have similar D50, but their particle size distributions may have different widths. One measure of the breadth of the particle size distribution is the ratio D75 / D25, which is the ratio of the size at which 75% of the particles by volume are smaller to the size at which 25% of the particles by volume are smaller. The ratio of the breadth of the particle size distribution, as measured by D75 / D25, may be between 40:1 and 1.1:1 for two different particle sizes.

[0029] Suitable particles include, but are not limited to, precipitated, colloidal, and pyrogenic metal oxide particles. Metal oxide particles can be manufactured using techniques known to those skilled in the art. Exemplary commercially available titania particles include Cerion's TiO-W1215 titania, Nyacol's TiSolB titania, and Cristal ACTiV S5-300B titania. Exemplary commercially available tin oxide particles include Nyacol's Sn15 tin oxide.

[0030] Precipitated metal oxide particles can be produced using conventional techniques and are often formed by agglomeration of the desired particles from an aqueous medium under the influence of high salt concentrations, acids or other agglomerating agents. The metal oxide particles are filtered, washed, dried and separated from the remainder of other reaction products by conventional techniques known to those skilled in the art. The precipitated particles are often aggregated, in the sense that many primary particles are agglomerated together to form somewhat spherical aggregated clusters. Non-limiting examples of commercially available precipitated metal oxides include Hi-Sil® products from PPG Industries, Inc. and Zeosil® products available from Evonik Corporation.

[0031] The production of fumed metal oxides is a well-documented process that involves the hydrolysis of a suitable feedstock vapor (e.g., aluminum chloride for fumed alumina, or silicon tetrachloride for fumed silica) in a flame of hydrogen and oxygen. Roughly spherical molten particles are formed in the combustion process, and particle size can be varied through control of process parameters. These molten spheres, also called primary particles, fuse together by undergoing collisions at their contact points to form branched three-dimensional chain-like aggregates. The formation of aggregates is believed to be irreversible as a result of fusion between primary particles. During cooling and collection, the aggregates undergo further collisions that may result in some mechanical entanglement to form agglomerates. It is believed that these agglomerates are loosely held together by van der Waals forces and can be returned, i.e., deagglomerated, by suitable dispersion in a suitable medium. Mixed or co-fumed metal oxide particles can also be produced utilizing conventional techniques known to those of skill in the art, including, for example, the conventional techniques described in Ettlinger et al., GB 2296915 A1, which is incorporated herein by reference in its entirety.

[0032] Alternative metal oxide morphologies can be obtained using methods disclosed in U.S. Patent Nos. 4,755,368, 6,551,567 and 6,702,994, U.S. Patent Publication No. 20110244387, Mueller et al., "Nanoparticle synthesis at high production rates by flame spray pyrolysis", Chemical Engineering Science, 58, 1969 (2003), and Naito et al., "New Submicron Silica Produced by the Fumed Process", presented at NIP28, International Conference on Digital Printing Technologies and Digital Fabrication 2012, 2012, p.179-182, the entire contents of which are incorporated by reference. Typically, these methods result in metal oxide particles with low structure and low surface area. Many of these particles are pyrogenic, i.e., they are produced in a flame. Other methods of making pyrogenic particles are disclosed, for example, in Kodas and Hampden-Smith, Aerosol Processing of Materials, Wiley-VCH, 1998. Suitable pyrogenic metal oxides for use in the composite particles provided herein are small, for example having a volume mean diameter of less than 200 nm.

[0033] Colloidal metal oxide particles are often non-aggregated, discrete (primary) particles, typically spherical or nearly spherical in shape, but may have other shapes (e.g., having a nearly elliptical, square, or rectangular cross section). Colloidal metal oxides are commercially available or can be prepared by known methods from a variety of starting materials (e.g., wet-process metal oxides). Typically, colloidal metal oxide particles are produced in a manner similar to precipitated metal oxide particles (e.g., they are aggregated from an aqueous medium), but remain dispersed in an aqueous medium (often water alone, or water with co-solvents and / or stabilizers). Metal oxide particles can be prepared, for example, from silicic acid derived from an alkaline silicic acid solution having a pH of about 9 to about 11, where the silicic acid anions undergo polymerization to provide discrete silica particles of the desired particle size in the form of an aqueous dispersion. Typically, colloidal metal oxide starting materials are available as sols, which are dispersions of colloidal metal oxide in a suitable solvent, which in many cases is water alone, or water with co-solvents and / or stabilizers. See, for example, Stoeber et al., "Controlled Growth of Monodisperse Silica Spheres in the Micron Size Range," Journal of Colloid and Interface Science, 26, 1968, pp. 62-69; Akitoshi Yoshida, Silica Nucleation, Polymerization, and Growth Preparation of Monodispersed Sols, Colloidal Silica Fundamentals and Applications, pp. 47-56 (eds. H. E. Bergna & W. O. Roberts, CRC Press: Boca Raton, Florida, 2006); and Iler, R. K., The Chemistry of Silica, p. 866 (John Wiley & Sons: New York, 1979). SeeNon-limiting examples of commercially available colloidal metal oxides suitable for use in the present invention include Nissan Chemical's SNOWTEX® products, LUDOX® products available from W.R. Grace & Co., NexSil™ and NexSil A™ series products available from Nyacol Nanotechnologies, Inc., Quartron™ products available from Fuso Chemical, and Levasil® products available from AkzoNobel.

[0034] The colloidal metal oxide particles may have a (volume-weighted) median particle size D50 of about 5 to about 300 nm, for example, about 5 to about 10 nm, about 10 to about 20 nm, about 20 nm to about 30 nm, about 30 to about 50 nm, about 50 to about 70 nm, about 70 to about 100 nm, about 100 nm to about 125 nm, about 125 nm to about 150 nm, about 150 nm to about 175 nm, about 175 nm to about 200 nm, about 200 nm to about 225 nm, about 225 nm to about 250 nm, about 250 nm to about 275 nm, or about 275 nm to about 300 nm. Of course, a mixture of particles with different volume-weighted median particle sizes D50 may contain particles having particle sizes in two or more of these ranges. The metal oxide particles may be spherical or non-spherical. For example, the aspect ratio of the metal oxide particles can be from about 1.5 to about 3, e.g., from about 1.5 to about 1.8, from about 1.8 to about 2.1, from about 2.1 to about 2.5, from about 2.5 to about 2.8, or from about 2.8 to about 3. Particle size is measured by disk centrifuge photosedimentation analysis or transmission electron microscopy according to the particle distributions described in the Examples below.

[0035] In one embodiment of making composite particles, metal oxide particles are treated with a first hydrophobization system. The first hydrophobization system may comprise one or more hydrophobization components. Preferably, the first hydrophobization system comprises at least one bifunctional component that comprises a first reactive group, such as a silane, that can be covalently or non-covalently bonded to the metal oxide particles, and a second reactive group that can be incorporated into the polymer of the metal oxide-polymer composite particles. In certain embodiments, the bifunctional component has a molecular weight less than 300. "Hydrophobic" metal oxide particles, as that term is used herein, include altering the level or degree of hydrophobicity. The degree of hydrophobicity imparted to the metal oxide particles varies depending on the type and amount of treatment agent used. Hydrophobic metal oxide particles for use according to the invention may have, for example, from about 15% to about 85% of the available metal oxide surface reacted hydroxyl groups, such as from about 25% to about 75% or from about 40% to about 65% of the available metal oxide surface reacted hydroxyl groups, or any percentage bounded by any two of the above endpoints. If a second hydrophobizing agent is used as discussed below, it will react to form covalent or non-covalent bonds with a portion of the hydroxyl groups on the surface of the metal oxide.

[0036] The bifunctional component has the formula [R 3 3-x (OR 1 ) x ]SiR 2 Q, x is 1, 2 or 3, R 1 is methyl or ethyl, R 2 is the general formula C n H 2n wherein n is 1 to 10; R 3 is methyl or ethyl, Q is a mercapto, glycidyl, or substituted or unsubstituted vinyl, acrylate ester or methacrylate ester group, with the proviso that when Q is substituted or unsubstituted vinyl, n is 2 to 10. The first hydrophobizing system has the formula (OR 1 ) 4-z SiR4 z where z is 1 or 2 and R 4 is a branched or unbranched C1 to C10 alkyl group or R 2 where Ph is an unsubstituted phenyl group or a phenyl group substituted with C1-C10 branched or unbranched alkyl, halogen, C1-C10 alkyl ether, methoxy, ethoxy or hydroxy. Exemplary agents suitable for use in the first hydrophobization system are (3-acryloxypropyl)trimethoxysilane, isobutyltrimethoxysilane, propyltrimethoxysilane, mercaptopropyltrimethoxysilane, glycidoxypropyltrimethoxysilane, (3-acryloxypropyl)triethoxysilane, 3-methacryloxypropyltrimethoxysilane, methacryloxypropyltriethoxysilane, methacryloxymethyltrimethoxysilane, methacryloxymethyltriethoxy ... Examples of suitable functional silanes include, but are not limited to, 3-methacryloxypropylmethyldimethoxysilane, 3-methacryloxypropyldimethylethoxysilane, 3-butenyltrimethoxysilane, 3-butenyltriethoxysilane, 4-pentenyltriethoxysilane, 4-pentenyltrimethoxysilane, 5-hexenetrimethoxysilane, 5-hexenemethyldimethoxysilane, 3-methacryloxypropyldimethylmethoxysilane, diisobutyldimethoxysilane, and diisopropyldimethoxysilane. If the metal oxide particles are not silica, then di- or tri-functional silanes should be used (i.e., x should be 2 or 3).

[0037] The solubility of the components of the first hydrophobization system may be between 10 and 0.06 g / L, preferably between 9 and 0.03 g / L, more preferably between 8 and 0.1 g / L, and most preferably between 7 and 0.5 g / L. It is theorized that if the solubility of the components of the first hydrophobization system is too high or too low, the components will not form a sufficient emulsion.

[0038] In some embodiments, preferably, R4 R is a branched or unbranched C1 to C10 alkyl group. 4 When R is a branched or unbranched C1 to C10 alkyl group, the triboelectric charge of the metal oxide-polymer composite particles is 4 It is higher when a group is used or when no monofunctional component is used at all. For example, the triboelectric charge magnitude of a toner using the above-mentioned metal oxide-polymer particles as an external additive at low temperature / low humidity (LL) conditions can be increased by at least 10%, for example up to 45%, for example 12% to 42%, 15% to 40%, 17% to 37%, 20% to 35%, 23% to 32%, or 25% to 30%, relative to a toner having metal oxide-polymer composite particles that do not contain a monofunctional component. Alternatively or in addition, the triboelectric charge magnitude of such a toner at high temperature, high humidity (HH) conditions can be increased by at least 9%, for example up to 33%, for example 12% to 30%, 15% to 28%, or 17% to 25%, relative to a toner having metal oxide-polymer composite particles that do not contain a monofunctional component. Typically, triboelectric charging at both HH and LL conditions changes with the addition of alkyl-containing monofunctional components, and the change in triboelectric charging at HH and at LL can be any combination of ranges selected from the list above.

[0039] In addition, at least a portion of the metal oxide particles can be treated with a second hydrophobizing agent, either before or after treatment with the first hydrophobizing system, or after formation of the metal oxide-polymer composite particles, in which case only the exposed surfaces of the metal oxide particles are treated. Preferred agents for use as the second hydrophobizing agent are silazane compounds, siloxane compounds, and silane compounds, as well as silicone fluids with some solubility in water, with or without a cosolvent. Mixtures of two or more agents can be used. Preferably, the silicone fluids for use as the second hydrophobizing agent have a number average molecular weight of up to 500. Examples of silane compounds include alkylsilanes and alkoxysilanes. Alkoxysilanes are represented by the general formula R' x Si(OR'') 4-xR' includes compounds having the formula: 30 Branched and straight chain alkyl, alkenyl, C3-C 10 Cycloalkyl and C6-C 10 aryl, and R″ is selected from the group consisting of C1-C 10 where x is an integer from 1 to 3. When the metal oxide particles do not contain silica, the use of di- or trifunctional silanes or siloxanes or silicone fluids as the second hydrophobing agent provides better bonding than monofunctional silanes.

[0040] Non-limiting examples of silane compounds that can be used as the second hydrophobizing agent described herein include trimethylsilane, trimethylchlorosilane, dimethyldichlorosilane, methyltrichlorosilane, allyldimethylchlorosilane, benzyldimethylchlorosilane, methyltrimethoxysilane, methyltriethoxysilane, isobutyltrimethoxysilane, dimethyldimethoxysilane, dimethyldiethoxysilane, trimethylmethoxysilane, hydroxypropyltrimethoxysilane, phenyltrimethoxysilane, n-butyltrimethoxysilane, n-octyltriethoxysilane, n-hexadecyltrimethoxysilane, n-octadecyltrimethoxysilane, and the like.Similarly, amine-functionalized alkylalkoxysilanes can be used.Non-limiting examples of useful siloxane compounds include octamethylcyclotetrasiloxane, hexamethylcyclotrisiloxane, and the like. Non-limiting examples of useful silazane compounds include hexamethyldisilazane (HMDZ), hexamethylcyclotrisilazane, octamethylcyclotetrasilazane, and the like. For example, HMDZ can be used to cap unreacted hydroxyl groups on the surface of metal oxide particles. Exemplary hydrophobicity-imparting agents also include hexamethyldisilazane, isobutyltrimethoxysilane, octyltrimethoxysilane, and cyclic silazanes, such as those disclosed in U.S. Pat. No. 5,989,768. Such cyclic silazanes have the formula: [ka] wherein R7 and R8 are independently selected from the group consisting of hydrogen, halogen, alkyl, alkoxy, aryl, and aryloxy; R9 is hydrogen, (CH2) r CH3 (wherein r is an integer from 0 to 3), C(O)(CH2) r CH3 (wherein r is an integer from 0 to 3), C(O)NH2, C(O)NH(CH2) r CH3 (wherein r is an integer from 0 to 3) and C(O)N[(CH2) r CH3](CH2) s CH3 (wherein r and s are integers from 0 to 3); R 10 is the formula [(CH2) a (CHX) b (CYZ) c X, Y and Z are independently selected from the group consisting of hydrogen, halogen, alkyl, alkoxy, aryl and aryloxy, and a, b and c are integers from 0 to 6, with the proviso that (a+b+c) is equal to an integer from 2 to 6. Cyclic silazanes are represented by the formula: [ka] and R may be a 5- or 6-membered ring having the formula 11 is the formula [(CH2) a (CHX) b (CYZ) c X, Y and Z are independently selected from the group consisting of hydrogen, halogen, alkyl, alkoxy, aryl and aryloxy, and a, b and c are integers from 0 to 6, with the proviso that (a+b+c) is equal to 3 or 4.

[0041] Suitable silicone fluids for use as second treatment agent include both non-functionalized silicone fluids and functionalized silicone fluids.Depending on the conditions used to surface treat metal oxide particles and the specific silicone fluid used, silicone fluid may be present as a non-covalently bonded coating or may be covalently bonded to the surface of metal oxide particles.Non-limiting examples of useful non-functionalized silicone fluids include polydimethylsiloxane, polydiethylsiloxane, phenylmethylsiloxane copolymer, fluoroalkylsiloxane copolymer, diphenylsiloxane-dimethylsiloxane copolymer, phenylmethylsiloxane-dimethylsiloxane copolymer, phenylmethylsiloxane-diphenylsiloxane copolymer, methylhydrosiloxane-dimethylsiloxane copolymer, hydroxyl functionalized or hydroxyl terminated siloxane, polyalkylene modified silicone and the like.For example, functionalized silicone fluids may include functional groups selected from the group consisting of vinyl, hydride, hydroxyl, silanol, amino and epoxy. The functional groups may be attached directly to the silicone polymer backbone or through an intermediate alkyl, alkenyl, or aryl group.

[0042] Alternatively or additionally, the metal oxide particles can be treated using dimethylsiloxane copolymers as disclosed in U.S. Patent Publication No. 2011 / 0244382, the contents of which are incorporated herein by reference. Exemplary dimethylsiloxane copolymers have the formula: [ka] wherein R1 is -H, -CH3, R2=-H, -CH3, and R3=-CH3, -CH2CH3, -CH2CH2CH3, CH2Ar, -CH2CH2Ar, -Ar, -CH2CH2CF3 or -CH2CH2-R f and R f is a C1-C8 perfluoroalkyl group, and R4 is -CH3, -CH2CH3, -CH2CH2CH3, -CH2CH2CF3 or -CH2CH2-Rf and R f is a C1-C8 perfluoroalkyl group; R5 is -CH3, -CH2CH3, -CH2Ar, -CH2CH2Ar or -Ar; R6 is -H, -OH, -OCH3 or -OCH2CH3; Ar is unsubstituted phenyl or phenyl substituted with one or more methyl, halogen, ethyl, trifluoromethyl, pentafluoroethyl or -CH2CF3 groups; n, m and k are integers, where n≧1, m≧0 and k≧0; and the copolymer has a molecular weight of 208 to about 20,000.

[0043] Alternatively or in addition, the second hydrophobizing agent may be a charge modifier. Any of the charge modifiers disclosed in US Patent Publication No. 2010 / 0009280, the contents of which are incorporated herein by reference, may be used herein. Exemplary charge modifiers include, but are not limited to, 3-(2,4-dinitrophenylamino)propyltriethoxysilane (DNPS), 3,5-dinitrobenzamido-n-propyltriethoxysilane, 3-(triethoxysilylpropyl)-p-nitrobenzamide (TESPNBA), pentafluorophenyltriethoxysilane (PFPTES) and 2-(4-chlorosulfonylphenyl)ethyltrimethoxysilane (CSPES). Charge modifiers containing nitro groups should be used to post-treat the metal oxide particles after the copolymer because the hydrogenated groups may reduce the nitro groups.

[0044] Alternatively or in addition to the second hydrophobizing agent, the metal oxide particles can be treated with a third hydrophobizing agent following formation of the metal oxide-polymer composite. The third treating agent can be a silicone fluid or an alkylhalosilane having a number average molecular weight greater than 500. Alkylhalosilanes have the general formula R' x SiR'' y Z 4-x-y where R′ and R″ are as defined above, Z is a halogen, preferably chlorine, and y is 1, 2 or 3.

[0045] Through interaction between the second and / or third hydrophobizing agents (when used after formation of the metal oxide-polymer particles) and the polymer component of the metal oxide-polymer composite particles, these agents can further treat the exposed polymer surfaces of the metal oxide-polymer composite particles.

[0046] The polymer used in the metal oxide-polymer composite particles may be the same or different from the polymer or copolymer of the first hydrophobization system. That is, if the first hydrophobization system includes one or more polymerizable groups, the same material can simply be used to form the polymer. In a particular implementation, the polymer of the bifunctional component is not a polyether. Alternatively or in addition, the polymer of the bifunctional component is a polymer of an acrylate or methacrylate. Alternatively or in addition, a crosslinker or a different monomer that can be copolymerized at the end group of the bifunctional component can be used. Suitable monomers that can be used to prepare the metal oxide-polymer composite particles include substituted and unsubstituted vinyl and acrylate (including methacrylate) monomers, as well as other monomers that polymerize by radical polymerization. Exemplary monomers include styrene, acrylate and methacrylate, olefin, vinyl ester, and acrylonitrile, and are readily available to those skilled in the art, for example from Sigma-Aldrich (Milwaukee, WI). Such comonomers may also be substituted with C1-C3 alkyl, halogen, and / or hydroxyl groups. Substituted comonomers include, but are not limited to, hydroxypropyl methacrylate, trifluoropropyl methacrylate, and alpha-methylstyrene. Any of these monomers can be used by themselves in the mixture to form the copolymer, or together with a crosslinker. Exemplary crosslinkers include divinyl-terminated types of difunctional components (e.g., silanes substituted with vinyl groups) or other well-known vinyl crosslinkers, such as divinylbenzene and ethylene glycol dimethacrylate. Alternatively or in addition, the copolymer or crosslinker can react with a silane. For example, a silanol-terminated siloxane polymer or a copolymer of formula (1) above can be used in conjunction with the first hydrophobization system. The comonomer or crosslinker can be added at the same time as the first hydrophobization system, or at a different time. The amount of crosslinker can be adjusted to control the degree of crosslinking in the final polymer.

[0047] Metal oxide-polymer composite particles can be produced by making a dispersion of metal oxide particles in a fluid containing a first hydrophobization system, an optional monomer, and an aqueous phase. Polymerization of the polymerizable species in the organic phase results in the composite particles. In one exemplary procedure, an emulsion or mixture is prepared in an aqueous medium, for example in water with an optional cosolvent, for example an alcohol, for example isopropyl alcohol, with the first hydrophobization system, the optional comonomer, the crosslinker, and the metal oxide particles in a ratio of about 0.5:40, for example about 1:about 1.5, about 1.5:about 2, about 2:about 3, about 3:about 10, about 15:about 30, or about 10:about 20 by weight (polymerizable species / metal oxide). The total amount of metal oxide particles and polymerizable species relative to the total amount of solvent can be about 5 wt% to about 45 wt%, for example, about 5 wt% to about 15 wt%, about 15 wt% to about 20 wt%, about 20 wt% to about 30 wt%, about 30 wt% to about 40 wt%, or about 40 wt% to about 45 wt%.

[0048] Optionally, the pH is brought to about 8.0-10 and the dispersion is stirred (typically for 1-3 h) while the temperature is held at 25-60° C. Following stirring, an initiator is introduced at a level of about 0.1 to about 4 wt % relative to the monomer, such as about 0.1 to about 0.5%, about 0.5% to about 1%, about 1% to about 1.5%, about 1.5% to about 2%, about 2% to about 2.5%, about 2.5% to about 3%, about 3% to about 3.5%, or about 3.5% to about 4%. The initiator can be introduced as a powder or as a solution in ethanol, acetone, or other water-miscible solvent. Suitable initiators include, but are not limited to, oil-soluble azo or peroxide thermal initiators, such as 2,2′-azobis(2-methylpropionitrile) (AIBN), benzoyl peroxide, tert-butyl peracetate, and cyclohexanone peroxide. A variety of suitable initiators are available from Wako Pure Chemical Industries, Ltd. (Osaka, Japan). The initiator can be dissolved in the monomer prior to the introduction of the metal oxide and distributed between the monomer and the aqueous phase. The resulting solution is incubated at 65-95°C with stirring for 4-6 h. The resulting slurry can be dried at 100-130°C overnight and the remaining solids are ground to form a powder. Other methods of separating the particles from the liquid can also be used to dry the particles. If a second hydrophobizing agent is added after formation of the metal oxide-polymer complex, it is introduced prior to the drying step. For example, a second hydrophobizing agent can be added and the slurry is stirred at 60-75°C for an additional 2-4 h.

[0049] Those skilled in the art will recognize that the particle size and shape of two or more groups of metal oxide particles and their ratio to each other in the reaction mixture, as well as changes in such solid loading in the mixture or emulsion, the ratio of polymer and metal oxide, the pH of the aqueous phase, and the incubation temperature will affect the morphology of the composite particles. In fact, for a given size of metal oxide-polymer composite particles, significant changes in the metal oxide particle size and the solid loading in the mixture or emulsion can be used to adjust the shape and graininess of the composite particles. In certain embodiments, the composite particles have metal oxide particles disposed in the composite particles, i.e., metal oxide particles that are completely in the polymer phase and protruding from the surface. In these embodiments, the metal oxide particles contribute to the mechanical reinforcement of the composite particles, increasing the compressive strength of the composite particles.

[0050] The degree of surface treatment of the metal oxide with the first hydrophobization system can be controlled by adjusting the pH and temperature of the starting solution. The rate of adsorption of the difunctional component and any monofunctional component onto the metal oxide particles (which can be subsequent to the formation of siloxane bonds between the surface and the respective component) can also be controlled by the selection of the leaving group on the silane-based difunctional or monofunctional component, for example ethoxy tends to hydrolyze slower than methoxy.

[0051] The particle size and particle size distribution of the metal oxide-polymer composite particles can be controlled by adjusting the proportions of metal oxide particles and the relative particle size and / or particle size distribution. To the extent that the particle size of the metal oxide-polymer composite particles is influenced by the particle size of the metal oxide particles, for a given composite particle made with a first metal oxide particle, the particle size of the composite particle can be increased by replacing at least a portion of the first metal oxide particle with a second metal oxide particle having a larger size. Similarly, replacing at least a portion of the first metal oxide particle with a second metal oxide particle having a smaller size will decrease the particle size of the resulting composite particle.

[0052] Regardless of the particle size distribution of the metal oxide particles, the coarseness of the metal oxide-polymer composite particles can be adjusted by modifying the reaction conditions. In general, increasing the pH of the reaction mixture, for example by adding ammonium hydroxide or using a base stabilized metal oxide dispersion, increases the coarseness or RTA. Reducing the solids loading in the reaction medium also increases the coarseness and RTA.

[0053] When a mixture of two groups of metal oxide particles is used, the ratio of the first metal oxide particles to the second metal oxide particles can be about 1:20 to about 20:1 by weight, for example, about 1:15 to about 15:1, about 1:10 to about 10:1, about 1:5 to about 5:1, or about 1:2 to about 2:1. The desired ratio of the first metal oxide particles to the second metal oxide particles can vary depending on the desired particle size of the composite particles and the particle sizes of the first and second metal oxide particles.

[0054] At least a portion of the metal oxide particles in the composite particle may be entirely embedded in the polymer portion of the composite particle. Alternatively or additionally, at least a portion of the metal oxide particles may be partially embedded in the polymer portion of the composite particle, i.e., a portion of the metal oxide particles protrudes in and out of the polymer matrix. In certain embodiments, when measured on metal oxide particles observable by electron microscopy of at least 200, preferably at least 500 metal oxide-polymer composite particles, the metal oxide particles exposed at the surface of the composite may have a length protruding from the surface of the metal oxide-polymer composite particle of about 0% to about 95%, for example, about 5% to about 90%, about 10% to about 20%, about 20% to about 30%, about 30% to about 40%, about 40% to about 50%, about 50% to about 60%, about 60% to about 70%, about 70% to about 80%, or about 80% to about 90%. The amount of metal oxide particles protruding from the surface of the metal oxide-polymer composite particles can vary depending on the size and / or shape of the metal oxide particles and the ratio of the particle size distribution (described as D75 / D25) or median particle size D50 of one or more populations of metal oxide particles.

[0055] The metal oxide-polymer composite particles may be round. Depending on the extent to which the metal oxide particles are exposed at the surface of the composite particle, round particles are not necessarily spherical, but are typically understood to have a "bumpy" surface. Alternatively, the use of two groups of metal oxide particles with a large particle size difference also results in the formation of anisometric particles. Such particles combine an irregular shape with high grain coarseness.

[0056] The shape and degree of "bumpiness" or roughness of metal oxide-polymer composite particles can be analyzed by TEM (transmission electron microscope) evaluation. Conventional image analysis software is used to define the perimeter P of the TEM image of the particle. The same software is used to calculate the particle image area S and to identify the maximum Feret diameter (Dmax) 20 across the particle, measured between two parallel lines 22 each tangent to the particle (see FIG. 1B). These measurements are suitable for multiple particles, preferably at least 100 particles, more preferably at least 500 particles, in multiple TEM images.

[0057] SF-1 indicates how much the particle shape deviates from spherical, and is expressed as 100(πDmax 2 / 4S). An ideal spherical particle has an SF-1 of 100. The higher the SF-1, the more the particle shape deviates from a spherical shape. The average SF-1 for the composite particles may be about 110 to 185, for example, about 110 to about 125, about 125 to about 150, or about 150 to about 185.

[0058] The grain size is P 2 / 4πS (John C. Russ, The Image Processing Handbook, CRC Press, 4th edition, 2002). FIG. 1B illustrates that roughness can be considered as the ratio of the area of ​​an imaginary circle 24 with a perimeter the same length as the perimeter 26 of the particle 28 to the area of ​​the real particle. The roughness of an ideal spherical particle is 1.0. However, the roughness of a spherical particle with a rough surface can be significantly greater than 1. Roughness is particularly sensitive to roughness and surface texture at very fine scales. Since the roughness formula includes both perimeter and image area, roughness is also an indication of the deviation of the particle shape, especially the deviation of the particle shape from a sphere. For example, the roughness for an ellipse with axes 1 and 2 is 1.19, and for an ellipse with axes 1 and 3 is 1.51. Thus, roughness increases with increasing surface roughness and increasing deviation of the particle shape from a sphere. The average roughness of the metal oxide-polymer composite particles may be between 1.15 and 1.9, for example between 1.15 and 1.2, between 1.2 and 1.5, between 1.5 and 1.7 or between 1.7 and 1.9. To improve free flow, the average roughness of the metal oxide-polymer composite particles is preferably greater than 1.22, for example greater than 1.25.

[0059] Alternatively or additionally, the same image analysis software can be used to draw a convex hull 30 on the image of the particle and determine the area C of the inside of the hull, called the "hull area". A convex hull is a curved convex that represents the boundary of the surface surrounding the entire particle. It is created by moving a pair of parallel lines until they are just tangent to the outside of the particle image. The angle of the parallel lines is then changed and the process is repeated until the entire path of the convex hull is defined. As shown in FIG. 1B, the convex hull resembles a rubber band stretched around the particle. The relative trough area (RTA) is defined by (CS) / S, where S is the area of ​​the particle image. The value of RTA increases with increasing protrusion from the surface. The RTA of a perfect sphere, ellipse or any hull is 0. The RTA of a typical non-aggregated colloidal silica is about 0.01. The average RTA of the metal oxide-polymer composite particles may be 0.01 to about 0.19, for example, about 0.03 to about 0.15, about 0.05 to about 0.13, or about 0.07 to about 0.11. To promote free flow of the toner, preferably the average RTA is greater than 0.06 or 0.08, for example, 0.06 to 0.13. The average RTA is measured using images of at least 100 particles, preferably at least 500 particles. Naturally, using more particle images provides higher sensitivity and facilitates differentiation of different particle morphologies.

[0060] Preferably, the metal oxide composite particles have an average SF-1 in the range or any subrange described above, and an average RTA in the range or any subrange described above. In addition, they may further have an average particle roughness in the range or any subrange described above. Particles having at least the average SF-1 and average RTA described above can show improved drop-off performance in toners relative to smoother or rounder particles.

[0061] Alternatively or additionally, the metal oxide-polymer composite particles may have a (volume weighted) median particle size or particle size D50 of about 20 nm to about 1000 nm. For example, the D50 of the metal oxide-polymer composite particles may be 20 nm to 100 nm, 100 nm to 200 nm, 200 nm to 300 nm, 300 nm to 400 nm, 400 nm to 500 nm, 500 nm to 600 nm, 600 nm to 700 nm, 700 nm to 800 nm, 800 nm to about 900 nm, or 900 nm to 1000 nm. The particle size of the metal oxide composite particles can be measured by disk centrifuge photosedimentation analysis.

[0062] As shown in the examples, toner cohesion increases with increasing particle size and decreases with particle "roughness" measured by RTA. Toner cohesion is inversely correlated with free flow. To improve toner free flow, preferably the metal oxide-polymer composite particles produced have a D50 of 40-75 nm, e.g., 40-70 nm or 40-65 nm, an average RTA of at least 0.06 or at least 0.08, e.g., 0.06-0.019, 0.08-0.015 or 0.08-0.13, and optionally an average particle roughness of at least 1.22, e.g., 1.25-1.60 or 1.70 or 1.22-1.35. Particles with a D50 smaller than 40 nm are expected to have a stronger tendency to embed into the toner surface, and particle size is inversely correlated with free flow performance.

[0063] In order to improve the anti-blocking property and prevent the toner particles from sticking to each other, preferably the metal oxide-polymer composite particles have a D50 of 100-150 nm, e.g. 105-150 nm or 110-150 nm, an average RTA of at least 0.06 or at least 0.08, e.g. 0.06-0.019, 0.08-0.015 or 0.08-0.13, and alternatively or additionally an average particle roughness of at least 1.22, e.g. at least 1.25 or at least 1.3, e.g. 1.25-1.60 or 1.70 or 1.22-1.35. The free-flowing performance of the toner tends to decrease with increasing size of the external additive. However, larger particles can better avoid being embedded in the soft toner surface. As the roughness of the composite particles increases, the free-flowing performance improves, weakening the effect of the increased size and optimizing the composite particles to maintain the anti-blocking property and free-flowing performance.

[0064] Preferably, the metal oxide-polymer composite particles have a density equal to or greater than the intrinsic density of the metal oxide itself (e.g., silica is 2.2 g / cm 3 and titanium dioxide has an intrinsic density of 3.6 g / cm 3 The composite particles have a density smaller than that of the metal oxide particles (having a density of 100% or less). For example, the intrinsic density of the composite particles may be about 30% to about 35%, about 35% to about 40%, 40% to about 45%, about 45% to about 50%, about 50% to about 55%, about 55% to about 60%, about 60% to about 63%, about 63% to about 67%, about 67% to about 70%, about 70% to about 73%, about 73% to about 76%, about 76% to about 79%, about 79% to about 82%, about 82% to about 85%, or about 85% to about 90% of the intrinsic density of the metal oxide particles contained therein. The density can be measured by helium pycnometer method. In some embodiments, the particle size and shape of the composite particles can be changed while maintaining the desired density by using metal oxide particles of different particle sizes in the composite. Maintaining a desired density allows one of ordinary skill in the art to reduce or maintain drop-off performance during fusing, maintain other properties of toner performance, or vary particle morphology without changing its refractive index.

[0065] The metal oxide-polymer composite particles can be used as external additives for both conventional and chemical toners. Conventional toners can be prepared by many known methods, such as mixing and heating the resin, pigment particles, optional charge enhancing additives and other additives in conventional melt extrusion and related equipment. Conventional equipment for dry blending of powders can be used to mix or blend the carbon black particles with the resin. Other methods include spray drying and the like. Generally, blending of the pigment and other ingredients with the resin is followed by mechanical attrition and classification to provide toner particles having the desired particle size and particle size distribution. Chemical toners, also known as chemically prepared toners, are manufactured in the liquid phase; generally, the resin particles are formed in the presence of a colorant. For example, processes have been developed in which a polymer latex is combined with an aqueous pigment dispersion and agglomerated using a flocculant to form polymer particles. Another process involves aqueous suspension polymerization of a dispersion of pigment in at least one monomer. Additionally, a pigment / polyester resin dispersion has been prepared and combined with water, and then the solvent is evaporated.

[0066] For both conventional and chemically prepared toners, the metal oxide-polymer composite particles can be combined with the toner particles in the same manner as conventional additives, such as fumed metal oxides or colloidal metal oxides. For example, the toner composition can be formulated by mixing a suitable amount of the metal oxide-polymer composite particles with toner particles having a suitable particle size in a blender. Alternatively or in addition, the metal oxide-polymer composite particles can be combined with the toner for use as an external additive by dry blending the toner particles with the core-shell composite particles using a Henschel or other suitable mixer, for example, using a mixer described in U.S. Pat. Nos. 9,470,993, 9,500,970, 9,575,425, JP 2019-095616, 2018-045006, or 2018-036596. Alternatively, the dispersion of metal oxide-polymer composite particles can be combined with the toner particles by wet blending methods, such as those disclosed in WO 2014 / 153355. For example, the toner can be sonicated with the dispersion of composite particles until a well-mixed dispersion is obtained. The toner particles having the metal oxide-polymer particles disposed or distributed on the surface of the toner particles can then be recovered from the dispersion, for example by vortexing and drying, or by other methods of recovering the particles from the dispersion. Alternatively or in addition, the metal oxide-polymer composite particles can be combined with the toner at the same time as other external additives, such as additional inorganic, composite or organic particles, or in a separate mixing step. A variety of particles for use as toner external additives are known to those skilled in the art and can be used in combination with one or more of the metal oxide-polymer composite particles provided herein. Exemplary external additives known to those skilled in the art include, but are not limited to, fumed silica, colloidal silica, titania, polymer particles, fatty acid salts, and other external additives suitable for use with toners. Typically, fumed silica and other naturally hydrophilic materials are rendered hydrophobic for use as toner additives.

[0067] In certain embodiments, the metal oxide-polymer composite particles comprise from about 0.5 wt% to about 7 wt% of the toner composition, such as from about 0.5 wt% to about 1 wt%, from about 1 wt% to about 1.5 wt%, from about 1.5 wt% to about 2 wt%, from about 2 wt% to about 2.5 wt%, from about 2.5 wt% to about 3 wt%, from about 3 wt% to about 3.5 wt%, from about 3.5 wt% to about 4 wt%, from about 4 wt% to about 4.5 wt%, from about 4.5 wt% to about 5 wt%, from about 5 wt% to about 5.5 wt%, from about 5.5 wt% to about 6 wt%, from about 6 wt% to about 6.5 wt%, or from about 6.5 wt% to about 7 wt% of the toner composition. The metal oxide-polymer composite particles can be distributed on the surface of the toner particles. Preferably, the surface coverage of the metal oxide-polymer composite particles is about 10% to about 90% of the toner surface, for example 10% to 20%, 15% to 25%, 20% to 30%, 25% to 35%, 30% to 40%, 15% to 80%, 25% to 75%, 30% to 70%, 35% to 65%, 40% to 60%, 45% to 55% or 10% to 45%. The suitable surface coverage of the metal oxide-polymer particles on the toner depends on other materials further used as external additives, such as inorganic particles or polymer particles, as well as the nature and composition of the toner and any carrier or developer used with the toner. The distribution of the metal oxide-polymer composite particles on the toner can be relatively uniform. For example, the coefficient of variation of the distribution of the composite particles in the toner may be less than 0.40, such as less than 0.30, for example 0.05 to 0.15, 0.10 to 0.20, or 0.15 to 0.25, as measured by scanning electron microscopy as described in U.S. Patent Application Publication No. 2015 / 0037719, the contents of which are incorporated herein by reference.

[0068] Preferably, the metal oxide-polymer composite particles exhibit a low level of drop-off, which can enhance the durability of the toner and improve print quality over long press times. Although the retention of the composite particles on the toner particles depends in part on the composition of the toner, surrogate tests can be used to compare the performance of the metal oxide-polymer composite particles with metal oxide particles of comparable size and shape. For example, tests similar to those described in US Patent Application Publication Nos. 2003 / 0064310, 2010 / 0009282, 2006 / 0240350, and US Patent No. 9568847 can be used.

[0069] The metal oxide-polymer composite particles should have sufficient mechanical strength to be mixed with toner particles by methods typically used by those skilled in the art, such as by use of a Henschel mixer or other fluidizing mixer or blender. Preferably, the metal oxide-composite particles have sufficient strength to survive collisions between toner particles (having metal oxide-polymer composite particles distributed on their surface) during the development cycle of an electrophotographic process. The mechanical strength of the particles can be evaluated by formulating a chemical toner with the composite particles. The toner / particle blend is then mixed with a carrier, such as a silicone-coated Cu-Zn ferrite carrier (particle size of 30-90 μm), to form a mixture with 2% (w / w) toner. This mixture is then placed in a mixing container at a filling rate of about 70% to about 90% and rotated in an agitator, called a three-dimensional mixer, that can move the mixing container in a rhythmic, three-dimensional motion. The mixing container is moved at a rotational speed of about 50 to about 70 revolutions / min in a volume of about 6 to about 8 times the volume of the container. Exemplary agitators include the Turbula mixer available from Willy A. Bachoven AG, the Inversina mixer available from Bioengineering AG, and the dynaMix 3-dimensional mixer from Glen Mills. After a specified time, the sample is analyzed by SEM. If the composite particles have sufficient mechanical strength, they will not flatten or deform during mixing. Any flattening or deformation will show up as a change in particle size in the SEM. In a preferred embodiment, the change in diameter of the metal oxide-polymer composite particles after 10 min of mixing is less than 25%, preferably less than 20%, for example less than 10%.

[0070] Alternatively or additionally, the metal oxide-polymer composite particles can be used as a cleaning aid. The function and method of use of cleaning aids are discussed in U.S. Pat. No. 6,311,037, the contents of which are incorporated herein by reference. Briefly, after an image is printed, a resilient blade removes excess toner from the photoreceptor. Abrasive particles can facilitate more complete removal of excess toner that would otherwise transfer to subsequent copies, resulting in a "shadow" effect in which a weak image of the previous copy appears in one or more subsequent copies. Generally, two different types of particles are currently used as cleaning aids. Milled or precipitated inorganic particles (e.g., metal oxides, nitrides, carbides) have suitable hardness and shape for abrasive cleaning applications. However, they have a wide particle size distribution. Larger particles may scratch the surface of the photoreceptor, and smaller particles may result in less clearance between the cleaning blade and the photoreceptor. Colloidal silica has a uniform particle size, but due to its smooth surface, it has limited cleaning capabilities. Metal oxide-polymer composite particles combine the advantages of both of these particles - they have an irregular surface interrupted by hard, abrasive metal oxide particles, as well as a narrow particle size distribution. Metal oxide-polymer composite particles for use as cleaning aids can be incorporated into the toner formulation or can be contained in a separate storage container from which they are transported to the copier drum near the cleaning blade.

[0071] Preferably, the metal oxide-polymer composite particles are in the form of a powder. Preferably, the metal oxide-polymer composite particles exhibit a low moisture content, such as less than about 10 wt% moisture, such as about 0% to about 3%, about 1% to about 4%, about 3% to about 5%, about 5% to about 7%, or about 7% to about 10% moisture, after equilibration at 25°C at a pressure of about 1 atm and a relative humidity of 50%. The moisture content can be measured by drying a 100 mg sample in a glass vial in an oven at 125°C for 30 min, discharging the sample (e.g., briefly by holding the sample under a Haug One-Point-Ionizer (Haug North America, Williamsville, NY)), and then loading the sample into an instrument that measures the mass of the sample after incubation for 20 min at a selected relative humidity value of 0 to 95%.

[0072] The metal oxide-polymer composite particle powder can be crushed or milled, or can be classified, for example, by sieving, filtering, air classification, or other methods known to those skilled in the art, as described in JP2018-036596A. The degree of aggregation of the metal oxide-polymer composite particle powder can be less than 70%, for example less than 60%, for example 10%-70%, 20%-60%, 30%-50%, or 25%-40%. The degree of aggregation can be measured in a Hosokawa PT-X powder tester equipped with a Digiviblo Model 1332A digital display vibrometer (Showa Sokki Co., Ltd). Sieves with openings of 38 μm (400 mesh), 75 μm (200 mesh), and 150 μm (100 mesh) are stacked in order from the bottom of the vibration table of the powder tester. The measurements are carried out at 23° C. and 60% relative humidity (RH). The vibration amplitude of the vibration table is pre-adjusted so that the displacement value of the digital display vibration meter is 0.60 mm (peak to peak). The metal oxide-polymer composite particles are equilibrated at 23° C. and 60% RH for 24 h, and then 5.0 g is weighed and placed on a 150 μm sieve on the top stage of the powder tester. The sieves are vibrated for 30 s, and then the mass of the composite particles remaining on each sieve is measured to calculate the degree of aggregation based on the following formula: Degree of aggregation (%) = {(mass of sample on a sieve with 150 μm openings (g)) / 5 (g)} × 100 + {(mass of sample on a sieve with 75 μm openings (g)) / 5 (g)} × 100 × 0.6 + {(mass of sample on a sieve with 38 μm mesh (g)) / 5 (g)} × 100 × 0.2

[0073] The metal oxide-polymer composite particles can be combined with toner particles to form a toner. Conventional toners can be prepared by many known methods, such as by mixing and heating the resin, pigment particles, optional charge enhancing additives and other additives in conventional melt extrusion and related equipment. Conventional equipment for dry blending of powders can be used to mix or blend the carbon black particles with the resin. Other methods include spray drying and the like. Generally, blending of the pigment and other ingredients with the resin is followed by mechanical attrition and classification to provide toner particles having the desired particle size and particle size distribution. Chemical toners, also known as chemically prepared toners, are manufactured in the liquid phase; generally, the resin particles are formed in the presence of a colorant. For example, processes have been developed in which a polymer latex is combined with an aqueous pigment dispersion and agglomerated using a flocculant to form polymer particles. Another process involves aqueous suspension polymerization of a dispersion of pigment in at least one monomer. Additionally, a pigment / polyester resin dispersion has been prepared and combined with water, and then the solvent is evaporated.

[0074] Metal oxide-polymer composite particles can provide various advantages to the toners in which they are used as external additives. For example, metal oxide-polymer composite particles can complement the performance of other external additives with which they are used in combination, such as fumed or sol-gel (colloidal) silica, titania, mixed metal oxides such as, but not limited to, strontium titanate and strontium zirconate, waxes, fatty acid salts, polymer particles, and other materials typically used to enhance the free-flow and triboelectric charging performance of the final toner product.

[0075] The present invention is further defined by the following examples, which are intended to be merely exemplary in nature. EXAMPLES

[0076] To prepare samples for TEM, the particles in the aqueous dispersion were diluted with ethanol and sonicated for 10 min in a probe sonicator. Sufficient dilution and dispersion is necessary to ensure that each individual particle is well separated from neighboring particles. For TEM analysis, the suspension was dropped onto a 200 mesh carbon-coated copper grid. TEM images were obtained on a JEOL JEM-1200 EX Microscope at an accelerating voltage of 80 kV. Typically, the image resolution was set to 2 nm / pixel for an image size of 2048 pixels x 2048 pixels. First, any non-uniform background in the image, if present, was corrected using ImageJ software available from the National Institutes of Health, and then the image noise was reduced and the contrast was enhanced by suitable digital filters. The image was then segmented into two images with separate images of each individual particle. The particle size and shape of each particle were determined using the ImageJ particle analyzer and then combined to obtain the shape and size distribution of all particles in the sample, except for aggregates containing multiple primary composite particles. The SF-1, particle roughness and RTA values ​​for the composite particles below are averages from measurements of at least 500 particles; values ​​for colloidal silica are averages from measurements of at least 100 particles.

[0077] To prepare samples for disk centrifuge photosedimentation analysis, a 0.05 wt% dispersion of the composite particles was prepared in reverse osmosis treated water containing 0.05 wt% Triton X-100 surfactant in a 15 mL glass vial, which was stirred for 20 min using an SMT UH-50 homogenizer with 50 watts output at 90% power, using a 3 mm along 136 mm titanium tip positioned 0.5 mm from the bottom of the vial.

[0078] To combine the toner with the composite particles, an IKA M 20 Universal mill was used to mix the silica-polymer composite particles with black polyester chemical toner having a particle size of about 8 μm from Sinonar Corp. to achieve a total surface coverage of 30%. Three 15 s pulses were performed followed by a 15 s cooling period to prevent the toner from overheating and melting.

[0079] The surface coverage rate C of the toner is calculated according to the following relationship: C = [w / (100%-w)] × [(ρ t ×d t ) / (π×ρ a ×d a )]×[(√3) / 2], where w is the wt% of the additive, and ρ t , d t , ρ a , d a are the density (ρ) and diameter (d) of the toner and additive particles, respectively. The additive particle size was measured by disk centrifuge photosedimentation analysis (CPS), and the additive density was measured by helium pycnometer method. The toner density was 1.2 g / cm 3 The particle size was estimated to be 8 μm.

[0080] The developer was prepared by mixing 2 parts by weight of the formulated toner with 98 parts of Cu-Zn ferrite carrier coated with silicone resin (carrier particle size 60-90 μm, Powdertech Co. Ltd.). The developer was conditioned at 30° C. and 80% relative humidity (corresponding to HH (high temperature / high humidity) conditions) or 18° C. and 20% RH (corresponding to LL (low temperature / low humidity) conditions) for several hours. After conditioning, triboelectric charging was developed by rolling the jar containing the developer at 185 rpm for 30 min on a roll mill. Triboelectric charging was measured using a Vertex T-150 tester from Vertex Image Products, Inc. 1 g of charged developer was placed in a Faraday cage. Toner blow-off from the carrier was performed using approximately 20 psi air jet for 1 min. The electrostatic charge on the toner remaining in the Faraday cage carrier was measured by an electrometer built into the Vertex tester, and the mass of the blown-off toner was determined as the difference in the weight of the Faraday cage before and after blow-off.

[0081] The cohesion rate of the toner was measured using a Hosokawa PT-X powder tester. 2 g of toner mixed with additives was placed on the top sieve of a stack of three sieves (75, 45 and 25 μm openings) and the sieves were vibrated at a frequency of 50-60 Hz with an amplitude of 1.0 mm for 20 s. The formula: Cohesion Rate % = (M t / M init )+(M m / M init )×0.6+(M b / M init ) × 0.2 × 100%, where M t , M m and M b are the weights of toner remaining in the upper, middle, and lower sieves, respectively, when the vibration is stopped, and M init is the initial sample weight.

[0082] Example 1: Synthesis of Composite Particles Using a Mixture of Snowtex O40 (ST-O40) and Snowtex O (ST-O) This example illustrates the gradual reduction in particle size of composite particles following the replacement of the larger ST-O40 colloidal silica with the smaller ST-O colloidal silica. For Example 1A, a 3000 mL four-neck round bottom flask equipped with a stirring motor, condenser, and thermocouple on top was charged with 909 mL of deionized water, 257 g of ST-O40 silica dispersion in water (manufactured by Nissan Chemical; ∼22 nm particle size, pH ∼4.0, concentration ∼41 wt%), and 4.56 g of 5 M aqueous ammonium hydroxide solution. The dispersion was stirred for ∼5 min and 131 g of 3-methacryloxypropyltrimethoxysilane (MPS, CAS#2530-85-0, Mw=248.3) was added. The temperature was increased to 50° C. and the mixture was stirred at 200 rpm for 3 h. 2,2'-Azobisisobutyronitrile (further abbreviated as AIBN, CAS#78-67-1, Mw=164.2) is added and the temperature is raised to 80°C for 30 min. After 90 min at 80°C, the reaction mixture is cooled to 65°C and filtered through a 200 mesh screen to remove any coagulum fragments. 23 g of 1,1,1,3,3,3-hexamethyldisilazane (HMDZ) is added to the mixture and the reaction is continued at 65°C for an additional 5-8 h, after which the reaction mixture is transferred to a Pyrex tray and dried at 120°C overnight.

[0083] Examples 1B-1D were prepared following the same procedure as described for Example 1A. The only difference is that a mixture of ST-O40 and ST-O silica (12 nm diameter, Nissan Chemical) is used (silica is added sequentially to the reaction flask). Table 1 below contains information on the amounts of chemicals used. Using this method, particles can be prepared with the median particle size listed in the table below (as measured by disk centrifuge photosedimentation analysis). The change in particle size does not necessarily significantly change the particle roughness or RTA. For example, the process of Example 1A can be used to prepare particles with an average SF-1 of 141-146, an average particle roughness of 1.29-1.32, and an average RTA of 0.092-0.097. The process of Example 1B can be used to prepare particles with an average SF-1 of 147-152, an average particle roughness of 1.27-1.30, and an average RTA of 0.090-0.096. 2A and 2B show how particles incorporating both types of silica particles can be produced using the compositions in Examples 1A and 1B, respectively, described below. [Table 1]

[0084] Example 2: Synthesis of Composite Particles Using Snowtex O40 (ST-O40) and a Mixture of ST-O40 and ST-OL This example illustrates the increase in particle size of composite particles following the replacement of the smaller colloidal silica ST-O40 with the larger ST-OL silica. The method of Example 1 is used with the amounts of reagents in Table 2 below to produce particles having the median particle size described. Figures 3A-3C illustrate how particles incorporating both types of silica particles can be produced using the compositions of each of Examples 2A-2C described below. The arrows in Figure 3B point to the ST-OL particles. Using the process of Example 2A, particles can be prepared with an average SF-1 of 128-134, an average grain size of 1.24-1.29, and an average RTA of 0.068-0.077. Using the process of Example 2B, particles can be prepared with an average SF-1 of 132-139, an average grain size of 1.23-1.28, and an average RTA of 0.063-0.073. Using the process of Example 2C, particles can be prepared having an average SF-1 of 140-144, an average particle coarseness of 1.27-1.31, and an average RTA of 0.057-0.067. [Table 2]

[0085] Example 3: Synthesis of composite particles with irregular shapes and relatively smooth surfaces The process of Example 1 can be used to produce particles having a median particle size D50 of 125-150 nm, such as those shown in Figures 4A and 4B, using ST-OL silica (45-50 nm particle size) instead of the silica described in Example 1, and with a monomer-to-silica ratio of 1.4. The process of Example 3 can be used to prepare particles having an average SF-1 of 131-152, an average particle coarseness of 1.21-1.36, and an average RTA of 0.045-0.079.

[0086] Example 4: Synthesis of composite particles with irregular shapes and high surface roughness The process of Example 1, except without the addition of ammonium hydroxide, can be used to produce particles such as those shown in Figures 5A and 5B, using Ludox AS-40 silica (WR Grace, 22 nm particle size, 40% solids in dispersion) instead of the silica described in Example 1, at a monomer-to-silica ratio of 2, and at a solids concentration of 5.4% in the reaction mixture. Using the process of this example, particles can be prepared with an average SF-1 of 144-162, an average particle coarseness of 1.49-1.65, and an average RTA of 0.108-0.142.

[0087] Example 5: Synthesis of composite particles with spherical shape and different surface roughness A) The process of Example 1 can be used with ST-O40 silica and with a monomer-to-silica ratio of 3 to produce particles with a median particle size D50 of 115-140 nm, such as the particles shown in Figures 6A and 6B. The process of this example can be used to prepare particles with an average SF-1 of 116-119, an average particle coarseness of 1.19-1.22 and an average RTA of 0.038-0.042.

[0088] B) The process of Example 1 can be used with ST-O silica and with a monomer-to-silica ratio of 1.25 to produce particles such as those shown in Figures 6C and 6D with a median particle size D50 of 45-70 nm, but with a particle size significantly greater than that of Example 5A. The amounts of reagents that can be used to produce the particles of both Examples 5A and 5B are listed in Table 3 below. Using the process of this example, particles can be prepared with an average SF-1 of 135-140, an average particle size of 1.22-1.25, and an average RTA of 0.079-0.086. [Table 3]

[0089] Example 6 - Comparative Example 1 TEM images of spherical colloidal silica with smooth particle surface, i.e. MP-1040 colloidal silica (Nissan Chemical Inc.), were collected and parameters describing particle shape were measured (Figure 7). The average SF-1 was 113, the average particle roughness was 1.15, and the average RTA was 0.030.

[0090] Example 7 This example illustrates the use of an alkylsilane as a monofunctional component in conjunction with a bifunctional component of the first hydrophobization system to increase the triboelectric charging of silica-polymer composite particles. For Examples 7A and B, a solution of 19 g of ST-O40 silica in 68 g of deionized water is stirred at room temperature, followed by the addition of 0.19 g of 5N ammonium hydroxide to a pH of about 9.3. A mixture of either a) 4.9 g of n-propyltrimethoxysilane (NPTMS) or b) phenyltrimethoxysilane (PTMS) with 4.9 g of MPS is added all at once. The temperature is then raised to 40° C. in the course of 1 h and held at the same temperature for 1.5 h. 0.1 g of AIBN is then added and the temperature is raised to 80° C. and held for 1.5 h. The reaction mixture is cooled to 65° C., followed by the addition of 2.5 g of hexamethyldisilazane and the mixture is kept at 65° C. for 3 h. The resulting precipitate is filtered by suction, washed with deionized water and dried under vacuum. The resulting cake is dried in an oven at 120° C. for several hours and then ground in an IKA mill.

[0091] For Example 7C, a solution of 45 g of ST-O40 silica in 160 g of deionized water is stirred at room temperature, followed by the addition of 0.48 g of 5N ammonium hydroxide to a pH of about 9.3. A mixture of 11.5 g of diisopropyldimethoxysilane (DIPDMS) with 11.5 g of MPS is added all at once. The temperature is then raised to 40° C. in 1.5 h and kept at the same temperature for 2 h. The temperature is then raised to 60° C. and the mixture is incubated for 45 min. 0.5 g of AIBN is then added and the temperature is raised to 75° C. and kept for 2 h. The reaction mixture is cooled to 65° C., followed by the addition of 4.3 g of hexamethyldisilazane and the mixture is incubated at 65° C. for 6 h. The resulting precipitate is filtered by suction, washed with deionized water and dried under vacuum. The resulting cake is dried in an oven at 120° C. for several hours and then ground in an IKA mill.

[0092] Using these methods, samples can be produced that are incorporated into toner at 30% coverage, such as those in Table 4 below. The column "Hydrophobic" indicates that in a methanol-water solution, the sample does not wet at methanol concentrations lower than the percentage stated, i.e., the material floats on the surface. In contrast, the process of Example 1A can be used to produce composite particles that can be used to produce toners with triboelectric charging at LL conditions of -52 to -50, and triboelectric charging at HH conditions of -22.5 to -21.5. The results show that the use of an alkyl silane in addition to MPS increases triboelectric charging, while the use of an aromatic phenyl silane does not increase triboelectric charging significantly. [Table 4]

[0093] Example 8 - Increasing graininess The method of Example 1, except without the addition of ammonium hydroxide, can be used with Ludox AS-30 silica (WR Grace, 12 nm, 30% solids loading in the dispersion) and Ludox AS-40 silica, with the amount of silica dispersion and water adjusted to maintain the solids loading and monomer-to-silica ratio, to produce metal oxide-polymer composite particles having the characteristics below (Table 5). The Ludox silica is stabilized with ammonium hydroxide to increase the pH of the reaction mixture and increase the coarseness of the resulting composite particles. [Table 5]

[0094] Example 9 - Positively charged composite particles The particles having the properties described in Examples 1A and 5B were further treated with a cyclic silazane. 300 g of the composite particle powder was placed in a 1 gallon Nalgene bottle and mixed with a cyclic silazane of the formula: [ka] R 11 The powders were sprayed with a mixture of 4.3 g or 5.5 g of cyclic silazane, where is -(CHCH(CH)CH-, respectively, and 10 mL of 2-propanol. The bottles were tightly sealed and rotated at approximately 90 rpm on a rotary mill for 1 h. The sealed bottles were left at room temperature overnight, after which the powders were transferred to Pyrex trays and deammoniated at 120 °C in a dry air oven for 3-4 h. The use of cyclic silazane treatment allows these composite particles to carry a positive charge, leaving the amine groups attached to the particle surface intact, without changing the particle morphology.

[0095] Example 10 - Comparative Example As described in U.S. Patent No. 7,811,540, HMDZ was used to grow ST-XL and ST-YL silica (each with a surface area of ​​60 m 2 and 45m 2 , Nissan Chemicals, Inc.) to obtain a 1 nm 2The same silica was treated with HMDZ as described in U.S. Pat. No. 8,455,165 and a cyclic silazane as described in Example 9 to produce hydrophobically treated particles with approximately 10 molecules of HMDZ per nm of silica surface. 2 Hydrophobically treated particles having 5-10 molecules of HMDZ and approximately 1.6 molecules of cyclic silazane per silica surface were produced. The resulting powder was ground in an IKA A11 laboratory mill (IKA Corporation) prior to use in Example 11.

[0096] Example 11 - Agglutination rate measurement Particles having the compositions and morphologies described in Examples 1A, 2A, 2C, 4, 5B, 8A, 8B and 9, particles of Example 10 and CAB-O-SIL TG-C110 colloidal silica (HMDZ treated silica with particle size of 115 nm, SF-1 of 111, average particle roughness of 1.23 and average RTA of 0.0256) were made into toners as described above with coverages selected from 15%, 30-32% and 45%. The cohesion of the toners was measured in triplicate.

[0097] JMP software package (version 12.0.1, SAS Institute, Inc.) was used for statistical analysis of the collected data. A linear regression model was used. In the regression model, toner cohesion rate was the dependent variable and toner surface coverage, additive particle size and additive morphology described as RTA were the independent variables. The model included an intercept, linear terms for toner coverage and particle size and a quadratic term for RTA. Only statistically significant terms were included with a p-value less than 0.05. The model did not show a relationship between surface treatment (i.e. HMDZ / cyclic vs. HMDZ alone) and toner cohesion rate. There were 100 results used in the model. R 2 was 81.4%, and the significance level for the F test was <0.0001.

[0098] A linear regression model was used to generate a response surface for toner cohesion as a function of additive particle size and RTA at toner surface coverages of 15, 30, and 45% (FIG. 8; solid lines are the functions generated by the model; dotted lines on either side indicate confidence limits). The response surface shows that the lowest cohesion is expected when mixing the model toner with additives having an RTA between 0.060 and 0.120. The results show that cohesion increases with increasing particle size and decreasing surface coverage. FIG. 9 shows plots of cohesion versus surface coverage for toners made with composite particles having the properties described in Examples 2A (dotted line) and 8B (solid line). The average RTA for samples made according to Example 8B is higher than the average RTA for Example 2A, indicating that increasing RTA reduces cohesion and increases free flow.

[0099] The foregoing description of preferred embodiments of the invention has been provided for purposes of illustration and description. It is not intended to be exhaustive or to limit the invention to the precise form disclosed. Modifications and variations are possible in light of the above teachings or may be acquired from practice of the invention. The embodiments have been chosen and described to explain the principles of the invention and application of the practice of the invention and to enable those skilled in the art to utilize the invention in various embodiments and with various modifications suited to the particular use expected. It is intended that the scope of the invention be defined by the claims appended hereto and their equivalents.

Claims

1. A metal oxide-polymer composite particle in powder form comprising a plurality of metal oxide particles and a polymer matrix, the metal oxide particles are surface-modified with a first hydrophobization system comprising a bifunctional component, through which the metal oxide particles are covalently bonded to the polymer matrix; the polymer of the polymer matrix is ​​a polymer or copolymer of the difunctional component; and The metal oxide-polymer composite particles have a median particle size D50 of 40-75 nm and an average relative trough area (RTA) of at least 0.

06.

2. A metal oxide-polymer composite particle in powder form comprising a plurality of metal oxide particles and a polymer matrix, the metal oxide particles are surface-modified with a first hydrophobization system comprising a bifunctional component, through which the metal oxide particles are covalently bonded to the polymer matrix; the polymer of the polymer matrix is ​​a polymer or copolymer of the difunctional component; and The metal oxide-polymer composite particles have a median particle size D50 of 100-150 nm and an average RTA of at least 0.

06.

3. 3. The composite particle according to claim 1 or 2, wherein the metal oxide particles have a unimodal particle size distribution.

4. The composite particle according to any one of claims 1 to 3, wherein the composite particle has an average particle coarseness of greater than 1.

22.

5. The composite particle according to any one of claims 1 to 4, wherein the composite particle has an average particle coarseness of greater than 1.

25.

6. 6. The composite particle according to claim 1, wherein at least a portion of the surface of the metal oxide-polymer composite particle is modified with a second hydrophobizing agent.

7. The composite particle according to any one of claims 1 to 6, wherein the average RTA is from 0.08 to 0.

13.

8. The composite particle according to any one of claims 1 to 7, wherein the metal oxide-polymer composite particle comprises at least 15% metal oxide.

9. The bifunctional component has the formula [R 3 3-x (OR 1 ) x ]SiR 2 Q, x is 1, 2 or 3, R 1 is methyl or ethyl, R 2 is represented by the general formula C n H 2n where n is 1 to 10 and R 3 9. The composite particle of claim 1, wherein n is methyl or ethyl, and Q is a substituted or unsubstituted vinyl, acrylate ester, or methacrylate ester group, with the proviso that when Q is a substituted or unsubstituted vinyl, n is 2 to 10.

10. 10. Composite particles according to any one of claims 1 to 9, wherein the first hydrophobization system further comprises a monofunctional component which is covalently bonded to the metal oxide particles.

11. The monofunctional component is of the formula (OR 1 ) 4-z SiR 4 z With R 1 is methyl or ethyl, z is 1 or 2, R 4 is a branched or unbranched C1 to C10 alkyl group or R 2 11. The composite particle according to claim 10, wherein Ph is an unsubstituted phenyl group or a phenyl group substituted with C1-C10 branched or unbranched alkyl, halogen, C1-C10 alkyl ether, methoxy, ethoxy, or hydroxy.

12. A toner composition comprising the metal oxide-polymer composite particles according to any one of claims 1 to 11 disposed against a surface of a toner particle.

13. A toner composition comprising toner particles mixed with a powder comprising metal oxide-polymer composite particles comprising a plurality of metal oxide particles and a polymer matrix, the metal oxide particles are surface modified with a first hydrophobization system comprising a bifunctional component through which the metal oxide particles are covalently bonded to the polymer matrix and a monofunctional component covalently bonded to the metal oxide particles; At least a portion of the surface of the metal oxide-polymer composite particles is modified with a second hydrophobizing agent, and the polymer of the polymer matrix is ​​a polymer or copolymer of the bifunctional component; and A toner composition, wherein the triboelectric charging of said toner at high temperature / high humidity (HH) conditions is at least 9% greater than the triboelectric charging of a toner comprising a control metal oxide-polymer composite in which said monofunctional component is replaced with said difunctional component.

14. 14. The toner composition of claim 13, wherein the triboelectric charging of said toner at low temperature / low humidity (LL) conditions is at least 10% greater than the triboelectric charging of a toner comprising a control metal-oxide polymer composite in which said monofunctional component is replaced with said difunctional component.

15. 15. The toner composition of claim 13 or 14, wherein the monofunctional component and the difunctional component both contain silane groups.

16. The monofunctional component is of the formula (OR 1 ) 4-z SiR 4 z With R 1 is methyl or ethyl, z is 1 or 2, R 4 The toner composition of any one of claims 13 to 15, wherein is a branched or unbranched C1 to C10 alkyl group.

17. The toner composition according to any one of claims 13 to 16, wherein the solubility of said monofunctional component is from 10 to 0.06 g / L, preferably from 9 to 0.03 g / L, more preferably from 8 to 0.1 g / L, and most preferably from 7 to 0.5 g / L.

18. 1. A method for making a composite particle, comprising the steps of: preparing an aqueous dispersion comprising metal oxide particles and a first hydrophobization system comprising a difunctional component and a monofunctional component, said difunctional component and said monofunctional component being chemically bonded to said metal oxide particles; adding a polymerization initiator to said aqueous dispersion to form metal oxide-polymer composite particles having metal oxide particles on the surface thereof, the polymer matrix of said metal oxide-polymer composite particles being a polymer or copolymer of said first hydrophobization system; and drying said metal oxide-polymer composite particles to form a powder. The method includes:

19. 20. The method of claim 18, further comprising the step of treating the metal oxide-polymer composite particles with a second hydrophobizing agent before or after the drying step to produce hydrophobized metal oxide-polymer composite particles.

20. 20. The method of claim 18 or 19, wherein the monofunctional component and the difunctional component both contain silane groups.

21. The monofunctional component is of the formula (OR 1 ) 4-z SiR 4 z With R 1 is methyl or ethyl, z is 1 or 2, R 4 The method of any one of claims 18 to 20, wherein is a branched or unbranched C1 to C10 alkyl group.

22. The bifunctional component has the formula [R 3 3-x (OR 1 ) x ]SiR 2 Q, x is 1, 2 or 3, R 1 is methyl or ethyl, R 2 is represented by the general formula C n H 2n where n is 1 to 10 and R 3 22. The method of any one of claims 18 to 21, wherein: is methyl or ethyl; Q is a substituted or unsubstituted vinyl, acrylate ester, or methacrylate ester group, with the proviso that when Q is substituted or unsubstituted vinyl, then n is 2 to 10.

23. 23. The method of any one of claims 18 to 22, wherein the dispersion further comprises one or more of styrene, substituted or unsubstituted acrylate or methacrylate monomers, olefin monomers, vinyl esters, or acrylonitrile.

24. 24. The method according to any one of claims 18 to 23, wherein the solubility of the monofunctional component is from 10 to 0.06 g / L, preferably from 9 to 0.03 g / L, more preferably from 8 to 0.1 g / L, and most preferably from 7 to 0.5 g / L.

25. A metal oxide-polymer composite particle in powder form comprising a plurality of metal oxide particles and a polymer matrix, the plurality of metal oxide particles comprises at least a first group of metal oxide particles and a second group of metal oxide particles, the first group of metal oxide particles having a different particle size, shape, or particle size distribution relative to the second group; the metal oxide particles are surface-modified with a first hydrophobization system comprising a bifunctional component, through which the metal oxide particles are covalently bonded to the polymer matrix; at least a portion of said plurality of metal oxide particles protrude in and out of said polymer matrix; said polymer matrix comprising a polymer or copolymer of said first hydrophobization system; At least a portion of the surface of the metal oxide-polymer composite particles is modified with a second hydrophobizing agent; and The metal oxide-polymer composite particles have an average SF-1 of 110 to 185 and an average RTA of 0.06 to 0.

19.

26. 26. The composite particle of claim 25, wherein the first hydrophobization system further comprises a monofunctional component covalently bonded to the metal oxide particle.

27. The bifunctional component has the formula [R 3 3-x (OR 1 ) x ]SiR 2 Q, x is 1, 2 or 3, R 1 is methyl or ethyl, R 2 is represented by the general formula C n H 2n where n is 1 to 10 and R 3 27. The composite particle of claim 25 or 26, wherein: is methyl or ethyl; and Q is a substituted or unsubstituted vinyl, acrylate ester, or methacrylate ester group, with the proviso that when Q is a substituted or unsubstituted vinyl, n is from 2 to 10.

28. The monofunctional component is of the formula (OR 1 ) 4-z SiR 4 z With R 1 is methyl or ethyl, z is 1 or 2, R 4 is a branched or unbranched C1 to C10 alkyl group or R 2 28. The composite particle according to claim 27, wherein Ph is an unsubstituted phenyl group or a phenyl group substituted with C1-C10 branched or unbranched alkyl, halogen, C1-C10 alkyl ether, methoxy, ethoxy, or hydroxy.

29. 29. The composite particle according to any one of claims 25 to 28, wherein the median particle diameters D50 of the first and second populations have a ratio of about 40:1 to about 1.5:

1.

30. 30. The composite particle of any one of claims 25 to 29, wherein the ratio D75 / D25 for the first group and the second group has a ratio of about 40:1 to about 1.1:

1.

31. 31. The composite particle of any one of claims 25 to 30, wherein the mass ratio of the first group to the second group is from about 1:20 to about 20:1, e.g., from about 1:15 to about 15:1, from about 1:10 to about 10:1, from about 1:5 to about 5:1, or from about 1:2 to about 2:

1.

32. The composite particles according to any one of claims 25 to 31, wherein the metal oxide-polymer composite particles have a volume average particle size of about 20 nm to about 1000 nm.

33. The metal oxide-polymer composite particles have an average roughness P of about 1.22 to about 1.

9. 2 The composite particle according to any one of claims 25 to 32, having a molecular weight of 1 / 4πS.

34. 34. The composite particle of any one of claims 25 to 33, wherein the polymer matrix comprises polymers of styrene, unsubstituted or substituted acrylates or methacrylates, olefins, vinyl esters and acrylonitrile, as well as copolymers and mixtures thereof.

35. A toner composition comprising the composite particles according to any one of claims 25 to 34 disposed on a surface of a toner particle.

36. 1. A method for making metal oxide-polymer composite particles, comprising: An aqueous dispersion comprising a first hydrophobizing system in an aqueous medium and at least a first population of metal oxide particles and a second population of metal oxide particles, said first population of metal oxide particles having a different particle size, shape or particle size distribution than said second population, said first hydrophobizing system being represented by the formula [R 3 3-x (OR 1 ) x ]SiR 2 Q is a difunctional component, x is 1, 2 or 3, R 1 is methyl or ethyl, R 2 is represented by the general formula C n H 2n where n is 1 to 10 and R 3 is methyl or ethyl, and Q is a substituted or unsubstituted vinyl, acrylate ester, or methacrylate ester group, with the proviso that when Q is substituted or unsubstituted vinyl, n is from 2 to 10; Incubating the dispersion for a predetermined period of time; adding a radical initiator to the dispersion: forming the chemical groups of said first hydrophobization system as part of a polymer, thereby forming metal oxide-polymer composite particles; and drying the metal oxide-polymer composite particles to obtain a powder The method includes:

37. 37. The method of claim 36, further comprising the step of treating at least a portion of the metal oxide particles with a second hydrophobizing agent, which can be performed either prior to the step of preparing the metal oxide-polymer composite particles or after the step of forming the metal oxide-polymer composite particles.

38. The first hydrophobizing system has the formula (OR 1 ) 4-z SiR 4 z A monofunctional component having the formula: 1 is methyl or ethyl, z is 1 or 2, R 4 is a branched or unbranched C1 to C10 alkyl group or R 2 38. The method of claim 36 or 37, further comprising a monofunctional component, Ph, where Ph is an unsubstituted phenyl group or a phenyl group substituted with C1-C10 branched or unbranched alkyl, halogen, C1-C10 alkyl ether, methoxy, ethoxy, or hydroxy.

39. 39. The method of any one of claims 36 to 38, wherein the D50 of the first group and the second group has a ratio of about 40:1 to 1.5:

1.

40. 40. The method of any one of claims 36 to 39, wherein the ratio D75 / D25 for the first group and the second group has a ratio of from about 40:1 to about 1.1:

1.

41. 41. The method of any one of claims 36 to 40, wherein the weight ratio of the first group to the second group is from about 1:20 to about 20:

1.

42. 42. The method of any one of claims 36 to 41, wherein the emulsion further comprises one or more of styrene, substituted or unsubstituted acrylate or methacrylate monomers, olefin monomers, vinyl esters, or acrylonitrile.

43. The method of any one of claims 36 to 42, wherein at least a portion of the metal oxide particles protrude in and out of the polymer matrix.

44. The method of any one of claims 36 to 43, wherein the metal oxide-polymer composite particles have a volume average particle size of about 20 nm to about 1000 nm.

45. 45. The method of any one of claims 36 to 44, wherein the intrinsic density of the metal oxide-polymer composite particles is from about 30% to about 90% of the intrinsic density of the metal oxide as measured by helium pycnometry.

46. The method of any one of claims 36 to 45, wherein the metal oxide-polymer composite particles have an average SF-1 of from about 110 to about 185 and an average RTA of from about 0.06 to about 0.

19.

47. The metal oxide-polymer composite particles have an average roughness P of about 1.22 to about 1.

9. 2 47. The method according to any one of claims 36 to 46, wherein the sigma-sigma ratio is 1 / 4πS.

48. A metal oxide-polymer composite particle produced by the method of any one of claims 18 to 24 or 36 to 47.

Citation Information

Patent Citations

  • TONER COMPOSITION AND MANUFACTURING METHOD THEREOF

    JP2009537031A

  • Method for preparing hydrophobic silica

    JP2010503604A

  • Toner additives comprising composite particles

    JP2013092748A

  • Toner additive containing composite material particles

    JP2015502567A

  • Toner additives comprising composite particles

    US20140295341A1